The K-segments of wheat dehydrin WZY2 are essential for its protective functions under temperature stress - Yang, Wenbo; Zhang, Linsheng; Lv, Hui; Li, He; Zhang, Yane; Xu, Yang; Yu, Jianing (Frontiers in Plant Science, 2015)
Dehydrins (DHNs), group 2 of late embryogenesis abundant (LEA) proteins, are up-regulated in most plants during cold, drought, heat or salinity stress. All DHNs contain at least one K-segment, which is believed to play a significant role in DHN function by forming an amphipathic helix. In previous studies, wzy2, an YSK2-type DHN gene, was isolated from the Zhengyin 1 cultivar of Triticum aestivum under cold and drought stress treatment conditions. Four WZY2 truncated derivatives were constructed to knock out the K-, Y- or S-segment, which potentially affect the function of the protein. In vivo assays of Escherichia coli viability enhancement, in vitro lactate dehydrogenase (LDH) activity protection and ex vivo protein aggregation prevention assays revealed that WZY2 acted as a protectant and improved stress tolerance during temperature variation. The results also showed that unlike the truncated derivative without K-segments, the derivative containing two K-segments had remarkable effects that were similar to those of full-length WZY2, indicating that the K-segment is the major functional component of WZY2. Moreover, compared with the other segments, the first K-segment might be the most critical contributor to WZY2 functionality. In general, this work highlights the behavior of DHNs in relieving cold stress ex vivo and the contribution of the K-segment to DHN function.